Smoking behaviour among young doctors of a tertiary care hospital in North India - Bhat, Muneer A.; Rashid, Haroon; Hamid, Shahnawaz; Hamid, Sajad; Ali, Sadaf; Khursheed, Rehana (International Journal of Research in Medical Sciences, 2017)
Background:Tobacco use is one of the biggest public health threats the world has ever faced. There are more than one billion smokers in the world. Almost half of the world's children breathe air polluted by tobacco. Aim of current study was to study the smoking trends among young doctors in a tertiary care institute in north India. Methods:A descriptive observational cross-sectional epidemiological study was conducted among 250 doctors of a tertiary care Hospital in Jammu & Kashmir (Sheri Kashmir Institute of Medical Sciences, SKIMS) during the two months of February-March, 2014. The predesigned tool adopted during data collection was a questionnaire that was developed at the institute with the assistance from the faculty members and other experts. Results:Among 250 participants, (20%) were smokers; among smokers, (76%) were regular smokers and (24%) were occasional smokers. Majority of smokers were in the age group of 21-30 years (80%) & started smoking between 11-20 years (70%). All of them were male (100%). No significant difference was observed among urban and rural students. Among smokers, majority (60%) was in the practice of smoking for last 6 months to 1 year and 26% smoked for <6 months; & (14%) smoked for more than 5 years .It was found more than half of the responding (60%) students used to smoke 5-9 cigarettes per day; 14% is <5 and 26% consumed 10 or more per day .Among smokers, peer pressure was found in 80% cases. (χ2 = 107, P <0.001). Among smokers, almost 20% had other addiction and among non-smokers only 5% had .Effect of parental smoking was significantly higher in smokers than non-smoker (χ2 = 66.2, P <0.001) .It was seen that peer pressure was the most important risk factor (60%) of initiation of smoking habit followed by parental influence (20%). Majority (78.4%) had no intention to quit in the next 6 months. Lack of Incentive (36.36%) and Addiction (27.27%) were the main reasons for not quitting. Conclusion:We need to create more awareness regarding hazards of smoking in general population especially in medical students, and afterwards provide psychological and pharmacological support for those who intend to quit, as medical students can themselves become a tool to fight this hazard at all levels.